Informatsionno-entropiinaya i fiziologicheskaya otsenka tipov morfofunktsional'nykh izmenenii serdtsa v protsesse dolgovremennoi adaptatsii cheleoveka k fizicheskim nagruzkam - Kozupitsa, G. S.; Ratis, Yu. L.; Ratis, E. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The aim of this study was to classify and evaluate the types of a heart's morphofunctional changes at the process of a permanent adaptation of an organism to physical loads used to develop the endurane of male swimmers. The informational-entropic approach used by the authors had allowed to give the quantitative integral evaluation of a human organism's harmony. The types of heart's morphological structures changes at the process of an organism aging adaptation to physical loads had been substantiated by the authors.